A Theory of Stock Price Responses to Alternative Corporate Cash Disbursement Methods: Stock Repurchases and Dividends - Ofer, Aharon R.; Thakor, Anjan V. (Journal of Finance, 1987)
This paper develops a model in which managers can signal their firms' true values by using either a dividend or a stock repurchase or both. The authors explain a number of stylized facts about these cash-disbursement mechanisms, particularly those concerning the relative magnitudes of stock price responses to dividends and repurchases. Most importantly, they explain why a stock repurchase elicits a significantly higher price response, on average, than a dividend announcement.